Teori External Criteria dan Implikasinya Terhadap Studi Hadis; Telaah Atas Pemikiran Michael Cook - Ghifari, Muhammad (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2024)
This article discusses the theory of External Criteria and its implications for hadiths, with a focus on the thoughts of Michael Cook. The External Criteria theory is an approach in the study of hadiths that uses criteria outside the hadith texts to determine their authenticity and genuineness. This article explains the background and development of the External Criteria theory, as well as Cook's role in developing this approach. Cook introduced the use of critical methods and historical analysis to evaluate the authenticity of hadiths. He argues that External Criteria such as historical consistency, social context, and critical methods can help identify hadiths that are questionable or not authentic. Furthermore, this article discusses the implications of the External Criteria theory for hadiths. One of the implications is the challenge of obtaining reliable sources to determine the External Criteria. The results of this research show that Michael Cook's thoughts have made an important contribution to the development of the External Criteria theory and the investigation of hadith authenticity. Researchers and academics can use this approach to gain deeper insights into the authenticity and genuineness of hadiths.